Fine chemicals from biological resources: the wealth from nature - Lajis, Md. Nordin (Universiti Pertanian Malaysia, 1995)
Man has exploited plants, animals and other microorganisms since the beginning of civilization for a great variety of purposes. In addition to providing food, clothing, fuel and timber, these bioresources also produce fine chemicals which have found widespread use as medicines, insecticides, fragrances, pigments etc. With the advent of biotechnology particularly in the field of genetic engineering and cell culture the interest to search for high value fine chemicals resurges due to the possibility of producing the desired products in more efficient, economical and environmentai friendly manner.